Simple algorithm for the removal of anomalous propagation (AP) from NEXRAD radar images - Charalampidis, Dimitrios; Kasparis, Takis; Jones, Linwood W. (My University, 1999)
An algorithm for NEXRAD reflectivity Quality Control (QC) is presented. This procedure yields an acceptable radar reflectivity product, with the effects of clutter and Anomalous Propagation (AP) removed. The semi-automated approach is faster and less operator interactive than the TRMM GVbox QC method, and it has the advantage of being more objective.